Odpowiedzi

2010-04-12T16:30:23+02:00
A) 3x-1=5x______/-3x
-1=2x_________/:2
x=-½

b) y-3=9-y_______/+y
2y-3=9_________/+3
2y=12_________/:2
y=6

c) 0,5z+6=z-1_______/*10
5z+60=10z-10________/-60
5z=10z-70_______/-10z
-5z=-70_________/:(-5)
z=14
2010-04-12T16:34:45+02:00
A)3x-1=5x
3x-(-5x)=1
8x=1/8
x=jedna ósma


b)y-3=9-y
y+y=9+3
2y=12/2
y=6
2010-04-12T17:02:00+02:00
A) 3x-1=5x
3x - 5 x = 1
-2x = 1 /: -2
x = - 0,5


b) y-3=9-y
y+y=9+3
2y=12 /:2
y=6


c) 0,5z+6=z-1
0,5z-z=-1-6
-0,5z=-7 /:-0,5
z=3,5